Estimation of biomass and carbon content in durian plantations, Malaysia - Darul’aludin, Nurul Syafikah; Engku Ariff, Engku Azlin Rahayu; Nik Hashim, Nik Hazlan; Zohari, Ahmad Fitri; Kusin, Mazlin (Universiti Teknologi MARA (UiTM), 2024)
The Durio zibethinus is one of the main crops introduced in Pahang, Malaysia. It has been widely planted and has grown to be one of Malaysia's major plantations, offering important ecological, economic, and social benefits. In this study, 92 durian trees from eight plots were sampled among those aged between 3 months to 10 years planted on slightly acidic soil with a mean value of pH 6.1. The allometric biomass equation was used to estimate the aboveground biomass (AGB). It is the species-specific volume equation with a diameter at breast height (DBH) as the main variable that could accurately determine the biomass of the durian tree. The morphological variables such as DBH, height, canopy width and ecological variables including soil pH and also other variables as age and were also determined. The oldest durian tree, which is 10 years old, has the highest AGB and carbon content which are 670.97kg per tree and 335.485kg per tree respectively. The Spearman’s rank correlation coefficient (ρ) was also used to determine the relationship between biomass and morphological variables and other variables. The results showed strongest positive correlation between biomass and DBH which is ρ =0.863 and the lowest is between biomass and canopy size, which is ρ =0.730. The relationship between biomass and height and canopy width showed moderate positive correlation which are ρ = 0.863 and 0.788 respectively. The durian tree also had the potential for carbon sequestration, especially among the older trees that store large amounts of biomass, which can mitigate the accumulation of carbon dioxide (CO2).